DIGITAL REFLECTIVE JOURNAL IN THE TRANSLATION CLASSROOM: DOES THE FORMAT CHANGE THE GAME? - Korol, Tetiana Hryhorivna (LLT Journal: A Journal on Language and Language Teaching, 2024)
Reflection is considered an integral part of modern translation classrooms, particularly within the framework of the social constructivist paradigm. To enhance its effectiveness, students' reflective activities should be supported with appropriate tools. This paper aims to compare the effectiveness of two formats of digital reflective journals. A mixed-methods research was conducted involving 34 third-year undergraduate translation students, who were divided into two sample groups (SG). They were instructed to accompany their translation submissions with reflective journal entries, either in a MS Word document (SG1) or in a digital reflective journal application (SG2). The research results indicated a statistically significant difference in the translation proficiency levels of students in the two SGs. Reflective journaling using a specific application resulted in better translation performance and higher quality journal entries over the term. This study highlights alternative approaches to reflective journal writing in translation classrooms. Future research could explore the evaluation of journal entries using digital tools.